Penulisan Transkrip Konsultasi Syariah sebagai Upaya Pengarsipan Tertulis Dewan Syariah Wahdah Islamiyah - Muhammad Yusram; Akhmad Hanafi Dain Yunta; Azwar Azwar (WAHATUL MUJTAMA': Jurnal Pengabdian Masyarakat, 2021)
The Sharia Council of Wahdah Islamiyah is one of the strategic institutions in the structure of Wahdah Islamiyah Organization that has many visual recordings related to sharia consultations delivered by citizens. Therefore, in order to obtain broader benefits, the Sharia Council of Wahdah Islamiyah considers it important to do a transcript on the sharia consultation video. This process is done by copying the data through the recorded visual video. During one month of transcript process, 23 transcript files of Sharia Consultation were collected which were divided into five commissions, namely: General Commission, Worship Commission, Usrah Commission, Akidah Commission and Muamalah Commission. The results of this transcript were sent to the official email of the Sharia Council of Wahdah Islamiyah as an archive. The archive of transcripts of Wahdah Islamiyah Sharia Consultation that has been typed, can be one of the references of the Sharia Council which contains a collection of Questions and Answers (Q&A) of the Sharia Council of Wahdah Islamiyah and can be printed into a book for wider benefit.